Про можливість електрохімічного кондиціювання осадів стічних вод - Молчанов, А. Д.; Вербовський, О. В.; Швед, Г. Б.; Фльорко, В. А. (Видавництво Державного університету “Львівська політехніка”, 1999)
In clause the infuence of a constant electrical pressure on water removal from active sediment of urban sewer treatment plant is described.
Keywords: 628.336.32